Urban job expansion, induced migration and rising unemployment : a formulation and simplified empirical test for LDCs ; Rural-urban migration and urban underemployment in Brazil - 283999 Todaro, Michael P.; Yap, Lorene Y. L. (New York : Agricultural Development Council, 1978)
28